(untitled) (Journal of Educational Sciences, 2020)
The concept of updating the content of education guides the teacher’s work towards the formation of common moral values, human kindness, a system of self-control and independent activity in a student. Updating the content of secondary education is associated with the provision of a new quality of education; with the strengthening of the personality orientation of education; with updating its content; with the establishment of an effective relationship between teacher assessment and student self-control; with the conversion of student and teacher reflexes into means of assessment. Students’ self-control over their educational activities when teaching subjects at school can allow them to gradually set learning objectives and independently evaluate their decisions; develop volitional activity, understand the individual parts of their educational activities, combine them into a common structure and interact with other classmates in solving the problems of their educational activities. A new level of quality education will be achieved through the formation and implementation of self-control of their educational activities in the learning process of students. The methods and tools used in a chemistry lesson that allow students to control their learning activities are discussed in the article. The above example from the section “Theory of electrolytic dissociation” of a school chemistry course shows the possibility of using a technological map as one of the methods for organizing students’ self-control over their educational activities. Based on the data of the pedagogical experiment, in which 52 students from Almaty schools participated, it was proved that the methods of self-control in learning positively affect the quality of learning outcomes in chemistry, which is associated with self-control of students over educational activities in chemistry in high school. Key words: quality of education, sustainable development, educational activities, self-control, technological map, content of updated education, assessment.